รูปแบบการพัฒนาภาวะผู้นำเชิงสร้างสรรค์ของผู้บริหารสถานศึกษาขั้นพื้นฐาน - ธรรมทัศนานนท์, สุธรรม (วารสารวิจัยทางการศึกษา คณะศึกษาศาสตร์ มหาวิทยาลัยศรีนครินทรวิโรฒ, 2019)
บทคัดย่อ การวิจัยมีวัตถุประสงค์เพื่อพัฒนารูปแบบการพัฒนาภาวะผู้นำเชิงสร้างสรรค์ของผู้บริหารสถานศึกษาขั้นพื้นฐานการวิจัยแบ่งเป็น 4 ระยะ คือ ระยะที่ 1 ศึกษาองค์ประกอบและตัวชี้วัดภาวะผู้นำเชิงสร้างสรรค์ฯกลุ่มผู้ให้ข้อมูล ได้แก่ ผู้ทรงคุณวุฒิ จำนวน 9 คน โดยการเลือกแบบเจาะจงระยะที่ 2 สภาพปัจจุบันและสภาพที่พึงประสงค์ภาวะผู้นำเชิงสร้างสรรค์ฯกลุ่มตัวอย่างได้แก่ ผู้บริหารสถานศึกษาและครูหัวหน้างานวิชาการ จำนวน 750 คน โดยการสุ่มแบบแบ่งชั้นระยะที่ 3 ตรวจสอบยืนยันรูปแบบการพัฒนาภาวะผู้นำเชิงสร้างสรรค์ฯ กลุ่มผู้ให้ข้อมูล ได้แก่ ผู้ทรงคุณวุฒิ จำนวน 9 คน โดยการเลือกแบบเจาะจงระยะที่ 4 การประเมินผลการนำรูปแบบการพัฒนาภาวะผู้นำเชิงสร้างสรรค์ฯ ไปใช้กลุ่มเป้าหมาย ได้แก่ ผู้บริหารสถานศึกษาที่สมัครใจเข้ารับการพัฒนา จำนวน 10 คน เครื่องมือที่ใช้ในการวิจัย ได้แก่ แบบสอบถามแบบสัมภาษณ์ แบบบันทึก แบบทดสอบและแบบประเมินสถิติที่ใช้ในการวิจัย ได้แก่ ค่าเฉลี่ยและส่วนเบี่ยงเบนมาตรฐาน ผลการวิจัยพบว่า 1. องค์ประกอบและตัวชี้วัดภาวะผู้นําเชิงสร้างสรรค์ของผู้บริหารสถานศึกษา ประกอบด้วย 3 องค์ประกอบ 9 ตัวชี้วัดผลการประเมินความเหมาะสมอยู่ในระดับมาก 2. สภาพปัจจุบันภาวะผู้นำเชิงสร้างสรรค์ฯ อยู่ในระดับมากและสภาพที่พึงประสงค์ฯ อยู่ในระดับมากที่สุด 3. รูปแบบการพัฒนาภาวะผู้นำเชิงสร้างสรรค์ฯ ประกอบด้วย 4 ส่วน ได้แก่ ส่วนที่ 1 หลักการและวัตถุประสงค์ ส่วนที่ 2 องค์ประกอบ ภาวะผู้นำเชิงสร้างสรรค์ที่ต้องพัฒนา ส่วนที่ 3 กระบวนการพัฒนาภาวะผู้นำเชิงสร้างสรรค์มี 5 ขั้นประกอบด้วย ขั้นที่ 1 การเตรียมความพร้อมการพัฒนา ขั้นที่ 2 ความจำเป็นในการพัฒนา ขั้นที่ 3 การดำเนินการพัฒนา ขั้นที่ 4 การนำไปใช้ ขั้นที่ 5 การประเมินผลการพัฒนา และส่วนที่ 4 การประเมินผลการดำเนินการผลการประเมินความเหมาะสมและความเป็นไปได้ของรูปแบบฯ อยู่ในระดับมาก 4. การประเมินการนำรูปแบบการพัฒนาภาวะผู้นำเชิงสร้างสรรค์ฯ ไปใช้ 4.1 ผลการทดสอบตวามรู้หลังการใช้รูปแบบการพัฒนาฯ สูงกว่ากอนใช้รูปแบบการพัฒนาฯ อยางมีนัยสําคัญทางสถิติที่ระดับ .01 4.2 ผลการศึกษาพฤติกรรมภาวะผู้นำเชิงสร้างสรรค์ พบว่า หลังการพัฒนาภาวะผู้นําฯ สูงกว่าก่อนการพัฒนาภาวะผู้นําฯ อย่างมีนัยสําคัญทางสถิติที่ระดับ .01 4.3 ผลการศึกษาความพึงพอใจ พบว่า ผู้บริหารสถานศึกษามีความพึงพอใจต่อรูปแบบการพัฒนาภาวะผู้นําเชิงสร้างสรรค์ฯ โดยภาพรวมอยูในระดับมาก คำสำคัญ: รูปแบบการพัฒนาภาวะผู้นำเชิงสร้างสรรค์ ผู้บริหารสถานศึกษาขั้นพื้นฐาน ABSTRACT The research objectives were to develop the model of creative leadership development of basic school administrators. The research was divided into four stages. The first stage was to study the components and indicators of creative leadership of basic school administrators and the samples were 9 experts by purposive sampling; 2) to study the current and desirable states of creative leadership of basic school administrators the samples were 750 directors and head of academic affair teachers by the stratified random sampling technique; 3) to assess the appropriateness of creative leadership development model of basic school administrators and the participants were 9 experts by purposive sampling techniques and 4) the implementation of creative leadership development model of basic school administrators. The target groups are 10 directors as volunteers for the program. The research instruments were questionnaire, semi-structure interview form, group discussion record form, test and questionnaire in satisfaction. The statistics used in data analysis were arithmetic mean and standard deviation. The results as follow; 1. The components and indicators of creative leadership of basic school administrators consisted of 3 main components and 9 indicators and the assessment in appropriation was at high level. 2. The current stage of creative leadership of basic school administrators was at the high level while the desirable state of creative leadership of basic school administrators was the highest level. 3. The model of creative leadership development of basic school administrators consisted of 4 components as such 1) principle and objectives; 2) the components of creative leadership which need to improve; 3) the process in creative leadership development consisting of 5 stages as such preparation for development, realization for the need in development, model development, implementation and evaluation in development; 4) the assessment from the process and the assessment in appropriation and possibility was at high level. 4. The implementation of creative leadership development model of basic school administrators. 4.1 The result of knowledge assessment after implementing the model of creative leadership development of basic school administrators was higher than before implementing with statistical significance at .01 level. 4.2 The result of creative leadership behavior study after implementing the model of creative leadership development of basic school administrators was higher than before implementing with statistical significance at .01 level. 4.3 The satisfaction analysis of administrators forwards to using the model of creative leadership development of basic school administrators as a whole was at high level. Key words: Model, Creative Leadership and Basic School Administrators